Event structure in Kurdish very short story for example : (1970-1980) - Moatasam Ahmad Hamadameen; Azad Mohamed Said (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The event is an important and fundamental basis in building the story in general and the very short story in particular. It plays, along with other elements, a major role in moving the character in the very short story in a specific time and place. Therefore, the event has a strong and complementary relationship with other elements such as (character, time, place) to build the very short story. Therefore, the event is the basic and important element in the very short story. Very short stories go by quickly because of their short duration and small size. It cannot be extended because its area is small, and therefore the narrator of very short stories pays great attention to the construction of events, and therefore the narrative cannot be extended, and only a short period of the character’s life can be described. Therefore, in very short stories, short events are chosen and the focus is on their construction. This research deals with the structure of events in the Kurdish short stories of the years (1970-1980). Very short stories of this period used all four types of structures, storytellers used more varied structures for event structures and few very short stories were built with parallel structures because very short stories are short and cannot tell more than one event.